High refresh rate and low power consumption AMOLED panel using top‐gate n‐oxide and p‐LTPS TFTs. Issue 4 (26th March 2020) - Yonebayashi, Ryo; Tanaka, Kohei; Okada, Kuniaki; Yamamoto, Kaoru; Yamamoto, Keiichi; Uchida, Seiichi; Aoki, Tomohisa; Takeda, Yujiro; Furukawa, Hiroaki; Ito, Kazuatsu; Katoh, Hiromi; Nakamura, Wataru
Abstract: A pixel circuit and a gate driver on array for light‐emitting display are presented. By simultaneously utilizing top‐gate n‐type oxide and p‐type low‐temperature polycrystalline silicon (LTPS) thin‐film transistors (TFTs), the circuits provide high refresh rate and low power consumption. An active‐matrix LED (AMOLED) panel with proposed circuits is fabricated, and driving at various refresh rate ranging from 1 to 120 Hz could be achieved. Abstract : A pixel circuit and a gate driver on array for light‐emitting display are presented. By simultaneously utilizing top‐gate n‐type oxide and p‐type LTPS TFTs, the circuits provide high refresh rate and low power consumption. An AMOLED panel with proposed circuits is fabricated, and driving at various refresh rate ranging from 1 to 120 Hz could be achieved.